1999
DOI: 10.1007/s000110050468
|View full text |Cite
|
Sign up to set email alerts
|

An experimental allergic conjunctivitis induced by topical and repetitive applications of Japanese cedar pollens in guinea pigs

Abstract: The present sensitisation/challenge procedures are unique in terms of topical application of antigen. The lack of any correlation between the levels of the anaphylactic antibodies and severity of anaphylactic symptoms, and the difference of CIS between the left and right eyes of an individual strongly suggest that the anaphylactic antibodies are formed in locally limited tissue surrounding an eye. The present method should be useful for analysing the mechanisms of allergic conjunctivitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 26 publications
0
22
0
1
Order By: Relevance
“…In the present study, we evaluated whether the histamine involvement in the causation of symptoms is altered during multiple pollen challenges in our recently developed guinea pig model for Japanese cedar pollen-induced allergic conjunctivitis. 10) In most clinical and experimental settings of ocular allergy, pharmacologically active compounds are usually applied as eye drops in order to localize them at a high concentration. 4,5,19,20) However, it is well known that topically applied drugs are rapidly drained into the nasopharyngeal cavity through the nasopharyngeal duct.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the present study, we evaluated whether the histamine involvement in the causation of symptoms is altered during multiple pollen challenges in our recently developed guinea pig model for Japanese cedar pollen-induced allergic conjunctivitis. 10) In most clinical and experimental settings of ocular allergy, pharmacologically active compounds are usually applied as eye drops in order to localize them at a high concentration. 4,5,19,20) However, it is well known that topically applied drugs are rapidly drained into the nasopharyngeal cavity through the nasopharyngeal duct.…”
Section: Discussionmentioning
confidence: 99%
“…Sensitization, Challenge, and Treatment with Drugs As previously described, 10) guinea pigs were sensitized systemically by intraperitoneal injections with the extractsϩ Al(OH) 3 twice within a week at a dose of 10 mg pollen protein/20 mg Al(OH) 3 /ml/animal/time. On the 21st day after the first sensitization, the sensitized animals were challenged by the dropping of a pollen suspension without Al(OH) 3 in each of their eyes at a dose of 2 mg pollens/10 ml/eye.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondly, eosinophils as well as mast cells play roles in the symptoms caused by the repetitive antigen challenge, and eosinophil granule proteins such as EPO were detected in the tear fluid, indicating that the model is well correlated with the pathophysiology of patients with allergic conjunctivitis. Yasuda et al have previously reported the benefits of repetitive antigen challenge models of allergic conjunctivitis in guinea pigs (25).…”
Section: Discussionmentioning
confidence: 99%